The Legitimacy of the "Narrow Path" - Orji, Cyril (Journal of ecumenical studies, 2025)
, precis:, Episcopalian/Anglican United States Bishop Pierre Whalon has opened a new vista, producing a book that can reawaken ecumenical discussions. The ramifications of this personal testament of faith of an avowed ecumenist will be felt beyond the Episcopal and Anglican communions. The book rekindles old debates and opens new ones. This essay is an attempt to set the parameters of the debate and highlight the strengths and weaknesses of the proposal. Interrogating Whalon's ideas, it fleshes out some key desirable points of his groundbreaking work, then raises questions that critique the general canon of eucharistic hospitality. The conclusion leaves open the possibility that the search for visible Christian unity lies elsewhere than in eucharistic hospitality.